2022
DOI: 10.3390/cosmetics9040082
|View full text |Cite
|
Sign up to set email alerts
|

Study Design on the Presence of Metals in Moisturisers, and Compliance with Regulation (EC) No. 1223/2009 of the European Parliament and of the Council of the European Union, on Cosmetic Products

Abstract: Metals are present in cosmetics due to deliberate addition by the manufacturers, contamination of raw materials, and/or contamination during their manufacture or storage. The objective of this work was to explore the metal content in the most-consumed moisturising creams on the Spanish market, to verify their degree of compliance with Regulation (EC) No. 1223/2009 of the European Parliament and of the Council of the European Union, regarding the presence of metals in cosmetics. The moisturisers were digested (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…This makes ICP-MS an essential tool for ensuring the safety and compliance of cosmetics, as it helps identify potential contaminants and ensures that products meet regulatory standards, safeguarding consumer wellbeing [ 250 ]. ICP-MS was used in many studies related to heavy metal analysis in cosmetics and proved to be a good choice for determining low analyte concentrations, thus allowing the evaluation of toxic and potentially toxic components in cosmetics [ 222 , 223 , 224 , 225 , 226 , 228 , 251 , 252 , 253 , 254 , 255 , 256 , 257 , 258 , 259 ].…”
Section: Ms Analysis Of Cosmetic Ingredientsmentioning
confidence: 99%
See 1 more Smart Citation
“…This makes ICP-MS an essential tool for ensuring the safety and compliance of cosmetics, as it helps identify potential contaminants and ensures that products meet regulatory standards, safeguarding consumer wellbeing [ 250 ]. ICP-MS was used in many studies related to heavy metal analysis in cosmetics and proved to be a good choice for determining low analyte concentrations, thus allowing the evaluation of toxic and potentially toxic components in cosmetics [ 222 , 223 , 224 , 225 , 226 , 228 , 251 , 252 , 253 , 254 , 255 , 256 , 257 , 258 , 259 ].…”
Section: Ms Analysis Of Cosmetic Ingredientsmentioning
confidence: 99%
“…In addition to many studies that are focused on trace metal analyses in cosmetic matrices like colored make-up products (as a lot of pigments contain metal compounds), Rujido-Santos et al [ 259 ] analyzed the metal content in the most commonly used moisturizing creams on the Spanish market, to verify their degree of compliance with [ 274 ] regarding the presence of metals in cosmetics, as they have various functions in formulations of these cosmetic products [ 275 ]. The study used a validated methodology based on microwave-assisted acid digestion of the samples followed by ICP-MS and showed that most of the analyzed products did not comply with Regulation (EC) No.…”
Section: Ms Analysis Of Cosmetic Ingredientsmentioning
confidence: 99%